Biocorrosion of stainless steel in an environment containing marine sulfate-red using bacteria : an electrochemical study - Ibrahim, Zaharah (2007)
One of the most characteristic features of microbial degradation is that it involves not individual organisms growing in axenic culture but rather mixed communities of species with differing but complementary metabolic capabilities. Often such consortia demonstrate structural as well as functional organisation and exist in the form of flocs or biofilms within which there are likely to be localized microenvironments, each with a particular combination of organisms and physico-chemical conditions. Such biofilms are ubiquitous in nature being found, for example, on soil and sediment particles, and on the surfaces of teeth, ships and off-shore oil production platforms. In controlled processes of biodegradation and biotransformation they are the active component of trickling filters and the various forms of immobilized cell and fixed bed reactors.